Improvement of liver function parameters in advanced HCV‐associated liver cirrhosis by IFN‐free antiviral therapies. Issue 7 (6th August 2015) - Deterding, K.; Höner zu Siederdissen, C.; Port, K.; Solbach, P.; Sollik, L.; Kirschner, J.; Mix, C.; Cornberg, J.; Worzala, D.; Mix, H.; Manns, M. P.; Cornberg, M.; et al.
Summary: Background: Successful antiviral treatment of decompensated hepatitis B with HBV polymerase inhibitors is associated with improvement of liver function. To what extent liver function also improves in cirrhotic patients with chronic hepatitis C receiving novel interferon‐free (IFN‐free) therapies is unknown. Aim: To study liver function in cirrhotic HCV patients receiving IFN‐free therapies. Methods: We here studied 80 consecutive patients with advanced HCV associated liver cirrhosis including 34 patients (43%) with Child B/C cirrhosis and 42 patients (53%) with platelet counts of <90.000/μL receiving different combinations of direct acting antivirals without interferon [sofosbuvir/ribavirin ( n  = 56), sofosbuvir/simeprevir ± ribavirin ( n  = 15) and sofosbuvir/daclatasvir ± ribavirin ( n  = 9)]. The majority of patients was infected with HCV genotype 1 ( n  = 50); HCV genotypes 2, 3 and 4 were present in 4, 24 and 2 patients, respectively. Results: Liver function parameters including albumin, bilirubin, cholinesterase and prothrombin time all improved in the majority of patients during antiviral therapy irrespectively of the underlying HCV genotype, however, with different kinetics. MELD scores improved until post‐treatment week 12 in 44% of the patients but worsened in 15%. A sustained virological response was achieved in 63% of the patients. HCV RNA relapse led to moderate ALT increases in 15/23 patients but was not associated with hepatic decompensations. Conclusion: This real‐world single centre study showed that interferon‐free treatment of hepatitis C patients with advanced liver cirrhosis restores liver function, and may thereby reduce the need for liver transplantations.